Francisco Granizo: The Poet who Calls Upon the Primitive Moment - Michelena Otero, Sofía Gabriela (2011)
This essay is dedicated to one of the most lucid and articulate poets of Ecuadorian poetry, Francisco Granizo Ribadeneira (Quito, 1925-2009). In the first part, the author unravels some of the biographical features of the poet, which allows the reader to approach Granizo’s life in a more humane and familiar way; get to know the child and the man he was, and thus, get an insight of some of the features shown in his poetry. Granizo never shared his intimate life; no one approached him to learn about his academic or diplomatic work. It is important, then, to recover his work as a poet and academic. Secondly, Michelena analyzes the most relevant thematic aspects in Granizo’s poetry. Firstly, love, the eternal estrangement with the loved one, which symbolizes and, at the same time, blends with Nature, with God, with the primitive moment, and, in the end, with death. Secondly, mysticism, the religious drive which rules the man-God relationship and makes the poetic voice constantly seek the absolute, that is, the Origin. Lastly, blasphemy, that chaotic, despairing, and contradictory moment that arises as a consequence of amorous and mystical failure.